Interaction of water with oxide thin film model systems. Issue 3 (22nd January 2019) - Sterrer, Martin; Nilius, Niklas; Shaikhutdinov, Shamil; Heyde, Markus; Schmidt, Thomas; Freund, Hans-Joachim
Abstract: Abstract : The interaction between water and oxide surfaces plays an important role in many technological applications and environmental processes. However, gaining fundamental understanding of processes at oxide–water interfaces is challenging because of the complexity of the systems. To this end, results of experimental and computational studies utilizing well-defined oxide surfaces help to gain molecular-scale insights into the properties and reactivity of water on oxide surfaces. This is a necessary basis for the understanding of oxide surface chemistry in more complex environments. This review highlights recent advances in the fundamental understanding of oxide–water interaction using surface science experiments. In particular, we will discuss the results on crystalline and well-defined supported thin film oxide samples of the alkaline earth oxides (MgO and CaO), silica (SiO2 ), and magnetite (Fe3 O4 ). Several aspects of water–oxide interactions such as adsorption modes (molecular versus dissociative), formation of long-range ordered structures, and dissolution processes will be discussed.